2018
DOI: 10.1002/cam4.1512
|View full text |Cite
|
Sign up to set email alerts
|

14‐3‐3ζ binds to hepatitis B virus protein X and maintains its protein stability in hepatocellular carcinoma cells

Abstract: Abstract14‐3‐3ζ, a phosphopeptide‐binding molecule, is reportedly overexpressed in the cancerous tissues of patients with hepatocellular carcinoma (HCC). Hepatitis B virus (HBV) protein X (HBx) draws intensive attention in HBV‐related HCC because it not only regulates HBV replication, but also promotes carcinogenesis by interacting with various tumor or antitumor molecules. This study is performed to investigate whether and how 14‐3‐3ζ interacts with HBx. The coimmunoprecipitation (Co‐IP) results showed that 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, the only two reported structures with pS/pTXX-COOH consensus peptides are those of 14-3-3γ with the influenza virus protein NS1 (4O46.pdb) and our recently reported 14-3-3σ complex with the synthetic papillomavirus 16E6 phosphopeptide (6TWZ.pdb 24 ), however, both of them have rather low resolution (2.8-2.9 Å) (Supplementary Table 1). Together with the henipavirus protein W binding to 14-3-3σ via its C-terminal motif III peptide RRMpSN-COOH 66 , the adeno-associated virus protein Rep68 binding to 14-3-3 proteins using its Cterminal motif III peptide RGHpSL-COOH 67 and the hepatitis B virus protein X binding to 14-3-3ζ via an internal motif I peptide RPLpSGP 68 , these examples illustrate that viral proteins commonly use their elements, efficiently mimicking the host 14-3-3-binding peptides, to hijack the cellular functions controlled by 14-3-3 proteins. One of the possible mechanisms is the 14-3-3-mediated stabilization of viral proteins to evade dephosphorylation and degradation, which may prolong the half-life and increase chances for successful replication and further infections 21,68 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the only two reported structures with pS/pTXX-COOH consensus peptides are those of 14-3-3γ with the influenza virus protein NS1 (4O46.pdb) and our recently reported 14-3-3σ complex with the synthetic papillomavirus 16E6 phosphopeptide (6TWZ.pdb 24 ), however, both of them have rather low resolution (2.8-2.9 Å) (Supplementary Table 1). Together with the henipavirus protein W binding to 14-3-3σ via its C-terminal motif III peptide RRMpSN-COOH 66 , the adeno-associated virus protein Rep68 binding to 14-3-3 proteins using its Cterminal motif III peptide RGHpSL-COOH 67 and the hepatitis B virus protein X binding to 14-3-3ζ via an internal motif I peptide RPLpSGP 68 , these examples illustrate that viral proteins commonly use their elements, efficiently mimicking the host 14-3-3-binding peptides, to hijack the cellular functions controlled by 14-3-3 proteins. One of the possible mechanisms is the 14-3-3-mediated stabilization of viral proteins to evade dephosphorylation and degradation, which may prolong the half-life and increase chances for successful replication and further infections 21,68 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 14-3-3 ζ-HBx interaction could be a potential therapeutic target for HBV-related hepatocellular carcinoma [51]. Over the past few years, research has shown that 14-3-3 proteins are key regulators of many processes, including mitosis and apoptosis in animals [85]. According to Kim et al, HBx induces apoptosis by inhibiting the association between 14-3-3 ε and Bax, thereby enhancing mitochondrial-Bax translocation and cytochrome C release [86].…”
Section: Role Of 14-3-3 In Dna Virusesmentioning
confidence: 99%
“…The acetylation may affect the interaction between 14-3-3ζ and HBV protein X. 75 We found seven lysine residues in 14-3-3ζ were acetylated in functional domain. These residues include the K3 and K9 in the N-terminal; the K49, K74, and K120 in the 14-3-3ζ binding pocket; and the K138 and K157 in an alpha helix that helps form the phosphor-binding pocket.…”
Section: Discussionmentioning
confidence: 71%
“…74 14-3-3ζ are phosphorylated binding proteins, which are overexpressed in cancerous tissues of patients with HCC. 75 We found that 12 Kac sites of 14-3-3ζ were identified and quantified in HCC. The acetylation may affect the interaction between 14-3-3ζ and HBV protein X.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation